Human rights and drug control: a new perspective - Bone, Melissa L. (A GlassHouse book, 2020)
Introduction -- The origin and value of human rights and human drug use -- Human rights and the drug policy binary -- The legal architecture behind the human rights and drug control frameworks -- Health rights, autonomy rights and the drug control framework -- Religious rights, related rights and the drug control framework -- Conclusion